2017
DOI: 10.21522/tijcr.2014.04.02.art011
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Drug Dosage Calculation Knowledge and Proficiency among Newly Hired Nurses in Private Tertiary Care Hospital, Islamabad, Pakistan

Abstract: Background: Drug dosage calculation and administration is important function of nurses. The key professional role of nurses is to ensure safe drug dosage calculation while performing medication administration. Medication errors are a common cause of adverse events that may result due to wrong drug dosage calculation. The assessment of nurse's knowledge related to drug dosage calculation has not been conducted at the time of commencing their employment in the study hospital. Purpose: The purpose of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The study had found that nurses' main problem in drug dosage calculation constituted giving post-operative analgesics without prescriptions (34.2%). The study further examined that multiple oral drugs' administration processes made nurses confused and they lacked proper calculation skills in this regard 5 . While in contradiction, a study conducted by the Medical Centre University of Malaysia revealed that staff nurses had a piece of average knowledge about I/V drug preparation and administration 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study had found that nurses' main problem in drug dosage calculation constituted giving post-operative analgesics without prescriptions (34.2%). The study further examined that multiple oral drugs' administration processes made nurses confused and they lacked proper calculation skills in this regard 5 . While in contradiction, a study conducted by the Medical Centre University of Malaysia revealed that staff nurses had a piece of average knowledge about I/V drug preparation and administration 12 .…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that the staff nurses' medication calculation ability is vital and has been associated with quick & prompt recovery among patients. Therefore, registered nurses' good knowledge and skills are an important indicator of adherence to safety protocols 5 . This study was aimed to assess the staff nurse' knowledge and skills related to drug calculations.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted in Norway showed nurses poor knowledge and highest mean risk of medication error calling the immediate attention as nurses regularly have complete responsibility for medication management and drug dosage calculation and administration (Simonsen, et al, 2014). current literature reports that there is evidence that deaths from medication errors have been on the rise (Aronson, 2009).…”
Section: Intravenous Drug Errorsmentioning
confidence: 99%
“…(2022) , newly qualified nurses scored the lowest points on proficiency in discussing openly and solving problems. Transition challenges amongst newly qualified nurses might have profound consequences for the profession and patient care ( Sultana, 2017 ). Despite efforts to reduce this theory-practice gap by incorporating more clinical placement hours into nursing education ( Directive, 2013 ), many newly qualified nurses still experience unpreparedness after graduation ( Masso et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%